TEACHERS’ PERCEPTION AND PRACTICES ON GIVING FEEDBACK ON STUDENTS’ WORK DURING ONLINE LEARNING - Kadek Nina Harnin; Ni Nyoman Padmadewi; Ni Luh Putu Eka Sulistia Dewi; Ni Komang Arie Suwastini (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2022)
The aims of this study focused on looking at teachers’ perception and practice of giving feedback and also their challenges of giving feedback during online learning. This study used a descriptive qualitative method and online questionnaire was used to collect the data. The result of this study found that, teacher had a positive perception on the process of giving feedback. About 90% of teachers revealed that feedback was given to communicate about the gaps in performance, teachers’ expectation, affirming the marks and providing chances for self-assessment. Moreover, for correcting errors, there were 80% of teachers corrected the errors and highlighted them and 90% of them used word feedback positively. Time management was the biggest challenge found from the teachers for giving individual feedback. Hence, it needs to be considered to use an effective and efficient technique or tool as an aid for teachers to give the feedback during online learning.